Polytopic fractional delivery of an HIV vaccine alters cellular responses and results in increased epitope breadth in a phase 1 randomized trialResearch in context - Maurine D. Miner; Allan deCamp; Nicole Grunenberg; Stephen C. De Rosa; Andrew Fiore-Gartland; Katherine Bar; Paul Spearman; Mary Allen; Pei-Chun Yu; Bryce Manso; Nicole Frahm; Spyros Kalams; et al. (EBioMedicine, 2024)
Summary: Background: Elicitation of broad immune responses is understood to be required for an efficacious preventative HIV vaccine. This Phase 1 randomized controlled trial evaluated whether administration of vaccine antigens separated at multiple injection sites vs combined, fractional delivery at multiple sites affected T-cell breadth compared to standard, single site vaccination. Methods: We randomized 90 participants to receive recombinant adenovirus 5 (rAd5) vector with HIV inserts gag, pol and env via three different strategies. The Standard group received vaccine at a single anatomic site (n = 30) compared to two polytopic (multisite) vaccination groups: Separated (n = 30), where antigens were separately administered to four anatomical sites, and Fractioned (n = 30), where fractions of each vaccine component were combined and administered at four sites. All groups received the same total dose of vaccine. Findings: CD8 T-cell response rates and magnitudes were significantly higher in the Fractioned group than Standard for several antigen pools tested. CD4 T-cell response magnitudes to Pol were higher in the Separated than Standard group. T-cell epitope mapping demonstrated greatest breadth in the Fractioned group (median 8.0 vs 2.5 for Standard, Wilcoxon p = 0.03; not significant after multiplicity adjustment for co-primary endpoints). IgG binding antibody response rates to Env were higher in the Standard and Fractioned groups vs Separated group. Interpretation: This study shows that the number of anatomic sites for which a vaccine is delivered and distribution of its antigenic components influences immune responses in humans. Funding: National Institute of Allergy and Infectious Diseases, NIH.